The Role of Social Media In The Dissemination Of Information To Consumers - Putri, Mega Bellatus Sodier Suparman; Rini Rahayu Kurniati; Ratna Nikin Hardati (Universitas Islam Malang, 2024)
The purpose of this research is to find out how social media functions in disseminating information about Ketan Duren Ala Nana Malang City to customers. Qualitative research method was used in this research. This research uses observation, semi-structured interviews, and audio and visual documentation as data collection methods. The location of this research is Villa Gunung Buring Jalan Band Palmerah No. 1A, Cemorokandang, Kedungkandang District, Malang City, East Java. In this research process, qualitative methodology was used for data collection. While source triangulation, time triangulation, and technique triangulation were used to verify the truth of the data. The research findings show that Ketan Duren Ala Nana Malang City has implemented information dissemination through social media quite well, but is assisted by resellers in Java. To disseminate information to consumers so as to get significant consumers.